WET/DRY CYCLING AND THE EFFECTS OF FIBER LOADING ON THE MECHANICAL PROPERTIES OF CEMENT COMPOSITES MIXED WITH KRAFT PULP-FIBER FROM SENGON (Falcataria Mollucana) WOOD - Budiman, Ismail; Fatriasari, Widya (Teknologi Indonesia, 2017)
Recently, pulp fiber-cement composites have found a practical application in the commercial market to replace hazardous asbestos fibers. For exterior applications, the effects of cyclical wetting and drying on the performance of cement composites were studied. The objective of this study was to investigate the influence of filling wood fibers in cement composites prior to and after a wet/dry cycling treatment. The testing of kraft pulp fiber filling consisted of a 3, 5, and 7% of volume fraction of the composite. The target density and water to cement ratio of the composites produced was 1.5 gcm -3 , with a 0.50 base on weight, respectively. Cement composites were formed and pressed into a mold to the targeted dimensions of 30 cm × 2.5 cm × 2.5 cm (length × width × thickness) for 24hours, before they were removed from the mold. They were then subjected into two curing system conditions. First, the boards were immersed in a water tank at 18 ± 2 °C for 28 days and then tested for their mechanical properties. Secondly, the samples were immersed in the same conditions as before, but followed by a wet/dry curing cycling for 6 times before the mechanical properties were tested. Mechanical characteristics were observed according to ASTM C293-94 for flexural strength and ASTM C116-90 for compressive strength by using a Universal Testing Machine (UTM). The addition of pulp fiber and the wet/dry cycling treatment gave a significantly linear effect on the mechanical properties of composites. The higher amount of wood fiber filling in the cement composites resulted in a lower flexural and compressive strength of the composites. Furthermore, the wet/dry cycling treatment tended to lower the flexural strength, but not the compressive strength of the composites.